Breast cancer in systemic lupus. (March 2017) - Bernatsky, S; Ramsey-Goldman, R; Petri, M; Urowitz, M B; Gladman, D D; Fortin, P F; Ginzler, E; Romero-Diaz, J; Peschken, C; Jacobsen, S; Hanly, J G; Gordon, C; et al.
Objective: There is a decreased breast cancer risk in systemic lupus erythematosus (SLE) versus the general population. We assessed a large sample of SLE patients, evaluating demographic and clinical characteristics and breast cancer risk. Methods: We performed case-cohort analyses within a multi-center international SLE sample. We calculated the breast cancer hazard ratio (HR) in female SLE patients, relative to demographics, reproductive history, family history of breast cancer, and time-dependent measures of anti-dsDNA positivity, cumulative disease activity, and drugs, adjusted for SLE duration. Results: There were 86 SLE breast cancers and 4498 female SLE cancer-free controls. Patients were followed on average for 7.6 years. Versus controls, SLE breast cancer cases tended to be white and older. Breast cancer cases were similar to controls regarding anti-dsDNA positivity, disease activity, and most drug exposures over time. In univariate and multivariate models, the principal factor associated with breast cancers was older age at cohort entry. Conclusions: There was little evidence that breast cancer risk in this SLE sample was strongly driven by any of the clinical factors that we studied. Further search for factors that determine the lower risk of breast cancer in SLE may be warranted.